PENGARUH PENDIDIKAN GIZI TERHADAP PENINGKATAN ASUPAN ZAT GIZI MAKRO, ZAT BESI DAN PENINGKATAN BERAT BADAN IBU HAMIL KEK - Monecha Sely; Emy Yuliantini; Yenni Okfriantini (Poltekkes Kemenkes Bengkulu, 2020)
Abstrak : Less Chronic Energy (LCE) and Anemia are among the most common malnutrition problems in pregnant women, caused by lack of energy, protein, and iron over long periods of time. LCE will give birth to LBW in newborns. Provision of nutrition education becomes an alternative for the prevention of LCE and LBW prevention problems. To prove the influence of nutritional nutrition, iron, and weight change in pregnant women LCE. Pre experimental for 1 month (30 days) in LCE pregnant women, using pre-design and posttest design group. Provision of nutrition education using the media of pocket book and given 4 times in 1 week. Further repeated with a recall of 3x24 hours for 4 weeks post- Intervention. Data analysis using paired Ttest dependent test. The results showed an increase in intake after being given nutritional nutrients both macro nutrients, Fe, and body weight. Statistically not applicable, based on paired T-test dependent test showed no effect of nutrition education given to macro nutrient intake level (energy p 0,526, protein p 0,619, fat p 0,552, and carbohydrate p 0,445). The wilcoxon test of nutritional education influence on intake of Fe yields not charitable result with p value of 0.913. While for weight there is a significant change after given nutrition education with p value 0,001.KEK, while for macro nutrient intake and no effect.Keywords: Nutrition Education, KEK, Macro Nutrition, Iron, Weigh